2018
DOI: 10.1259/bjr.20170653
|View full text |Cite
|
Sign up to set email alerts
|

15O-H2O PET/CT as a tool for the quantitative assessment of early post-radiotherapy changes of heart perfusion in breast carcinoma patients

Abstract: O-HO PET/CT is safe and effective for the early detection and quantitative analysis of subclinical post-RT changes in heart perfusion in breast cancer patients. The LV segments supplied by the LAD are the main site of MBF changes. A minimum radiation dose deposited in the LAD may be a predictor of radiation-induced heart toxicity. Advances in knowledge: This is the first time that O-HO PET/CT has been used to assess MBF after RT and the first granular description of the distribution of blood flow changes after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Cardiotoxicity from radiation can be measured in many ways. [52][53][54]. One study [52] found statistically significant changes in perfusion occurred in 86% of patients 2 months after RT, and were independent of left-or right-sided breast cancer.…”
Section: Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiotoxicity from radiation can be measured in many ways. [52][53][54]. One study [52] found statistically significant changes in perfusion occurred in 86% of patients 2 months after RT, and were independent of left-or right-sided breast cancer.…”
Section: Heartmentioning
confidence: 99%
“…Myocardial perfusion imaging, initially with 201 Tl, a physiological potassium analogue, and later with superior technetium-based tracers (like [ 99m Tc]Tc-sestamibi or [ 99m Tc]Tc-tetrofosmin) have also been used to measure radiation-induced cardiotoxicity in breast cancer patients [ 50 ], finding higher abnormality rates in left-sided breast cancer patients (71% of left-sided breast cancer patients and 17% of right-sided breast cancer patients) [ 51 ]. More recently, there are studies that have used PET perfusion tracers like [ 15 O]H 2 O and [ 15 N]NH 3 to do the same [ 52 – 54 ]. One study [ 52 ] found statistically significant changes in perfusion occurred in 86% of patients 2 months after RT, and were independent of left- or right-sided breast cancer.…”
Section: Overview Of Possibilitiesmentioning
confidence: 99%
“…In recent precision cardio-oncology, it is a promise direction that applies combined omic-data and metabolic-function nuclear images (117), such as single-photon emission computed tomography (SPECT) (118) and positron emission tomography (PET) (119)(120)(121)(122). Of these, PET that demonstrated metabolic changes of the heart is the most expecting image marker for detecting RACVD.…”
Section: Challenges Of Clinical Detection For Racvdmentioning
confidence: 99%
“…The hypothesis that ABC-guided radiation would reduce perfusion defects had to be rejected, however, as perfusion defects were found at a similar frequency in the apex and the anterior wall in both groups. While PET studies on myocardial perfusion imaging in patients undergoing cardiotoxic treatment are scarce and delivered controversial results (84,85), an experimental study in dogs that underwent local heart irradiation clearly demonstrated myocardial perfusion defects on N-13 ammonia PET/CT (86). Interestingly, the irradiated dogs' hearts demonstrated an initial increase in perfusion after 3 months, a reduced perfusion after 6 months and a perfusion defect after 12 months.…”
Section: Myocardial Perfusion Imaging (Mpi)mentioning
confidence: 99%